Global, regional, and national epilepsy of unknown cause incidence and mortality, 1990–2036: cross-national health inequalities and predictive analytics - Wang, Yi; Wang, Yichen; Qiu, Xinyu; Yu, Zhenjie; Wang, Lijun (Frontiers in Neurology, 2025)
BackgroundThe responsibility for the disease burden associated with epilepsy of unknown cause is unevenly distributed across different nations. It is crucial to describe and forecast cross-national health disparities in terms of years lived with disability (YLDs) for the forthcoming 15-year period. We examined and projected trends in the burden of disease and cross-national inequalities in epilepsy of unknown cause globally, by region and country from 1990 to 2036.MethodsOur dataset, sourced from the Global Burden of Disease Study 2021, details the number of deaths, morbidity instances, and YLDs due to epilepsy of unknown cause. The distribution of YLDs across varying levels of sociodemographic indices (SDI) was quantified using the slope index of inequality (SII) and the relative concentration index (RCI). Additionally, autoregressive integrated moving average models were utilized to predict future trends in SII and RCI. We used Bayesian age-period-cohort (BAPC) models to predict global, national, and regional trends in age-standardized mortality rates (ASDR), age-standardized incidence rates (ASIR), and age-standardized young-onset rates (ASYR) for epilepsy of unknown cause over the next 15 years. We excluded countries or regions with a total number of age-group cases <5 (42 cases in total) because of potential problems with the sparsity of age-group data in countries with very small populations, resulting in the non-convergence of the BAPC model.ResultsIn 2021, epilepsy of unknown cause was responsible for 0.14 million deaths worldwide, with 3.27 million morbidity cases and 7.27 million YLDs recorded. Correlation analysis revealed a significant negative association between ASDR, ASYR, and SDI, while ASIR showed a weak and statistically insignificant positive correlation with SDI. The 1990–2021 SII and RCI values for epilepsy of unknown cause YLDs have been negative. The SII and RCI for YLDs show a continuing downward trend, which is expected to continue over the next 15 years. Projections for the next 15 years show that both ASIR (71.04%) and ASYR (55.74%) will increase in most countries or regions while ASDR (75.41%) will decrease in most countries or regions.ConclusionHealth inequalities in the world’s idiopathic epileptic YLDs will continue to increase in the future, and the disease burden of idiopathic epileptic YLDs will become more concentrated in low-income countries.